2016
DOI: 10.1038/srep23755
|View full text |Cite
|
Sign up to set email alerts
|

Micropapillary: A component more likely to harbour heterogeneous EGFR mutations in lung adenocarcinomas

Abstract: The micropapillary (MP) subtype has recently been established to be a distinct marker of poor prognosis in lung adenocarcinomas (LACs). According to the 2015 WHO classification system, LAC constituents are required to be precisely reported. T790M mutation and an insertion in exon 20 (E20ins) are associated with EGFR-TKI resistance. A total of 211 LAC patients were involved in this study, and EGFR mutations were determined using an amplification refractory mutation system (ARMS). Sex, smoking history, lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In the present study we found that sub-clonality for KRAS or EGFR mutation was associated with shorter survival times. The presence of sub-clonality for the common drivers in lung adenocarcinoma is in accordance with some previous reports [ 7 , 8 , 10 , 15 , 16 ]. However, different cohorts report lack of sub-clonality [ 17 ] or claim that it is probably a rare condition [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study we found that sub-clonality for KRAS or EGFR mutation was associated with shorter survival times. The presence of sub-clonality for the common drivers in lung adenocarcinoma is in accordance with some previous reports [ 7 , 8 , 10 , 15 , 16 ]. However, different cohorts report lack of sub-clonality [ 17 ] or claim that it is probably a rare condition [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, even within the same lesion, multi-region sampling provided evidence for sub-clonality for EGFR mutation status [ 13 , 14 ] and for ALK rearrangement [ 15 ]. In one study, EGFR sub-clonality was specifically linked to micropapillary histological variant [ 16 ]. On the other hand, an analysis of 862 cases with EGFR mutations did not find dual mutations and different areas of the tumor as well as paired primary and metastasis were concordant for the mutation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A higher proportion of solid or micropapillary pattern refers to worse prognosis. Local recurrence, nodal involvement and distant metastases are more frequent among these neoplasms [9]. Some authors have found that even 1% [10][11][12][13] or 5% [5,[14][15][16][17][18] of these components may cause an unfavourable outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians and oncologists turn on comprehensive therapies combined to targeted treatment and immune checkpoint inhibitors. Molecular discordances between primary and metastatic tumors differ among histological types [4]. A subset of patients with EGFRmutant LACs fosters MRs to EGFR-TKIs.…”
Section: Introductionmentioning
confidence: 99%